Policy Conflict Framework: Analisis Konflik Pembangunan Wisata Alam Alaska di Kota Batu - Saputra, Yoga Aldi (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
The emergence of a decision in the form of public policy is very prone to conflict. This can be caused by many factors such as target groups who do not need or benefit from policies, target groups are not aware of the benefits they receive, or even target groups reject policies because they are not supporters of policy implementers. Policy conflicts have to do with issues related to a large number of interests in the process of determining and enforcing policies. Conflicts in tourism involve many stakeholders with diverse values and complex interaction dynamics, both between local communities and the government, between local communities and tourists, between companies and the government, and between local communities and tourism companies. The phenomenon of conflict occurs in the development of Kasinan pedestal nature tourism or known as Alaska tourism located in Pesanggrahan Village, Batu District, Batu City. Through the perspective of the policy conflict framework, it can be analyzed related to the nature of conflict from the groups involved, the intensity of conflict, the causes of conflict in terms of context and process, and feedback consisting of output and outcome.